A unique database for gathering data from a mobile app and medical prescription software: a useful data source to collect and analyse patient-reported outcomes of depression and anxiety symptoms. (2nd October 2017) - Watanabe, Yoshinori; Hirano, Yoko; Asami, Yuko; Okada, Maki; Fujita, Kazuya
Abstract: A unique database named 'AN-SAPO' was developed by Iwato Corp. and Japan Brain Corp. in collaboration with the psychiatric clinics run by Himorogi Group in Japan. The AN-SAPO database includes patients' depression/anxiety score data from a mobile app named AN-SAPO and medical records from medical prescription software named 'ORCA'. On the mobile app, depression/anxiety severity can be evaluated by answering 20 brief questions and the scores are transferred to the AN-SAPO database together with the patients' medical records on ORCA. Currently, this database is used at the Himorogi Group's psychiatric clinics and has over 2000 patients' records accumulated since November 2013. Since the database covers patients' demographic data, prescribed drugs, and the efficacy and safety information, it could be a useful supporting tool for decision-making in clinical practice. We expect it to be utilised in wider areas of medical fields and for future pharmacovigilance and pharmacoepidemiological studies.